Fire down below - Golding, William, 1911-1993.; Faber & Faber (London : Faber & Faber, 1989)
Having gone to the Pink Hotel to get some sleep, Fireman Small detects a fire there and saves its animal guests.
English.
Keywords: Animals -- Fiction; English, Fiction